2015
DOI: 10.1111/joor.12327
|View full text |Cite
|
Sign up to set email alerts
|

Success, clinical performance and patient satisfaction of direct fibre‐reinforced composite fixed partial dentures – a two‐year clinical study

Abstract: To evaluate the success, clinical performance and patient satisfaction of directly placed fibre-reinforced composite (FRC) fixed partial dentures (FPDs) in 2 years. One hundred sixty-seven FRC FPDs (120 subjects) were directly fabricated to restore a single missing tooth by six Advanced Education in General Dentistry (AEGD) residents. The FRC FPDs recipients were randomised into two groups according to the fibre materials (pre-impregnated glass or polyethylene). Clinical performance was evaluated at baseline (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…The bonding surface on the anterior teeth was also smaller than the entire bonding surface of the inlay cavities. A recent study reports the great success of the FRC‐FPD after a 2‐year follow‐up …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bonding surface on the anterior teeth was also smaller than the entire bonding surface of the inlay cavities. A recent study reports the great success of the FRC‐FPD after a 2‐year follow‐up …”
Section: Discussionmentioning
confidence: 99%
“…Direct FRC FDPs can be reliable treatment options for replacement of single missing teeth in some anterior and posterior areas. 6,12,14,16,18,19 Some in vitro studies have shown that inlay box preparations, 7,20 the length of the glass fibers, 4,21 and the design of various pontics 22 influenced FRC-FPD's resistance to fracture. After reporting an improvement of removable denture fracture strength by using glass fiber reinforcements 23 the research question for this study was: what would be the in vivo behavior of anterior and posterior d-FRC-FPDs?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that in the earlier studies, limited load-bearing capacity was reported as a disadvantage of FRC fixed partial prosthesis and most common failures in FRC was reported as delamination of veneering composite at pontic area, the recent studies indicates that survival rate is quite high up to five years, which reflects material development and learning of fabricating FRC FPDs. 15,[25][26][27] This clinical report presented two cases in which FRC fixed partial prosthesis were successfully used to restore anterior edentulous spaces by using a natural tooth and a composite crown as a pontic. Fiber reinforced composite resin bridges can be used for temporary restorations up to the completion of the development and growth in pediatric dentistry as a lead until implant or conventional prosthetic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…3,25 In the present cases, the preparations of the two abutment teeth were performed according to the literature minimally and confined to enamel, it was a noninvasive approach. Further more for deciding the treatment option, the parental cooperation was held and they stated that their children could dislike wearing removable prosthesis and they preferred an adhesive bridge taking in to account the remaking more than one time until the completion of the growth period.…”
Section: Discussionmentioning
confidence: 99%